Retinoblastoma binding protein 7 is involved in Kiss1 mRNA upregulation in rodents - Kei HORIHATA; Naoko INOUE; Yoshihisa UENOYAMA; Kei-ichiro MAEDA; Hiroko TSUKAMURA (The Society for Reproduction and Development, 2020)
Kisspeptin, encoded by Kiss1, is essential for reproduction in mammals. Kiss1 expression is regulated by estrogen via histone acetylation in the Kiss1 promotor region. Thus, elucidation of histone modification factor(s) involved in the regulation of Kiss1 expression is required to gain further understanding of the mechanisms of its control. The RNA-seq analysis of isolated kisspeptin neurons, obtained from the arcuate nucleus (ARC) of female rats, revealed that Rbbp7, encoding retinoblastoma binding protein 7 (RBBP7), a member of histone modification and chromatin remodeling complexes, is highly expressed in the ARC kisspeptin neurons. Thus, the present study aimed to investigate whether RBBP7 is involved in Kiss1 expression. Histological analysis using in situ hybridization (ISH) revealed that Rbbp7 expression was located in several hypothalamic nuclei, including the ARC and the anteroventral periventricular nucleus (AVPV), where kisspeptin neurons are located. Double ISH for Rbbp7 and Kiss1 showed that a majority of kisspeptin neurons (more than 85%) expressed Rbbp7 mRNA in both the ARC and the AVPV of female rats. Further, Rbbp7 mRNA knockdown significantly decreased in vitro expression of Kiss1 in a mouse immortalized kisspeptin neuronal cell line (mHypoA-55). Estrogen treatment significantly decreased and increased Kiss1 mRNA levels in the ARC and AVPV of ovariectomized female rats, respectively, but failed to affect Rbbp7 mRNA levels in both the nuclei. Taken together, these findings suggest that RBBP7 is involved in the upregulation of Kiss1 expression in kisspeptin neurons of rodents in an estrogen-independent manner.